Tik-Tok as a video-based teaching tool to enhance hearing impaired student’s english elementary vocabulary - Carrera Rivera, Christian Josué (2023)
This research paper investigates the potential of Tik-Tok, a popular video-sharing social media platform, as a video-based teaching tool to enhance the English elementary vocabulary of hearing-impaired students. The study is conducted within a public institution with a sample size of five hearing-impaired students. The research aims to address the difficulties faced by hearing-impaired students in acquiring and expanding their English vocabulary and explore innovative approaches to enhance their learning experience. The literature review highlights the use of video-based teaching tools and the benefits of Tik-Tok as an educational platform. The theoretical framework emphasizes the importance of specialized teaching approaches for hearing-impaired students and the potential benefits of incorporating technologies like Tik-Tok as visual aids in teaching English vocabulary. The methodology includes content analysis and document analysis to analyze Tik-Tok videos created for vocabulary learning and relevant documents discussing the use of video-based teaching tools for hearing-impaired students. The findings from this research will provide valuable insights into the effectiveness of Tik-Tok as a visual aid for enhancing vocabulary development in hearing-impaired students. Overall, this study contributes to the exploration of innovative approaches to support the English vocabulary acquisition of hearing-impaired students.